Describing Anesthesia Ready Time (ART) in the Anesthesia Services at the Central Surgical Installation of Banjarnegara Islamic Hospital - Dita Arum Aditrisna; Made Suandika; Amin Susanto (LPPM Universitas Harapan Bangsa, 2023)
The use of time in anesthesia services in central surgical installations can be seen in the quality of service provided by health workers to patients. There are many factors that cause anesthesia services to take a long time. This study aims to determine the description of anesthesia ready time (ART) in anesthesia services at the Central Surgery Installation (IBS) of Banjarnegara Islamic Hospital. The research method uses quantitative data with a descriptive observational approach. The sampling technique used was purposive sampling, and the sample size according to the inclusion criteria was 128 respondents from elective surgery patients using spinal anesthesia and general anesthesia and classified as ASA I-IV status. The data collection technique is observation using ART. The results of the study showed that ART was in the good category, resulting in 114 respondents, consisting of 45 respondents with general anesthesia and 69 respondents with spinal anesthesia. Conclusion: Anesthesia services at the central surgical installation of RSI Banjarnegara are categorized as good according to international measurements using ART.